Rethinking Development: Poverty and Inequality in the Global South - Ghimire, Rajendra (Dhammacakka Journal of Buddhism and Applied Buddhism, 2025)
The international development system promotes global progress across all sectors through cooperation, collaboration, and assistance. However, this system, dominated by wealthy nations, often exacerbates income inequality and poverty, particularly in the Global South. Despite foreign aid, trade, and investments intended to reduce poverty, the disparity between rich and poor countries persists. Moreover, the role of multilateral institutions and development agencies often deepens, rather than alleviates, the challenges of poverty and inequality in these regions. The objective of the paper is to explain and examine the unequal status of the development system, poverty in the Global South compared to the global north. In the development race, the developed and rich countries go beyond their area for the development of the world, as their concern is to develop the world mutually. While conducting different development activities throughout the developing countries, the developed countries have considerable interest in the market and resources. Negative consequences of globalization, lack of capacity of developing countries in competition over market, and specific policies implemented to the developing countries are the primary reasons for the poor countries to manage inequality and poverty. As the WTO, IMF, and World Bank help in trade policies, assistance and loan to the developing countries they provide different set of rules to be followed by developing countries. Therefore, globalization, poverty, income inequality and dependency are the primary reasons for the gap of development in the global south. A library-based analytical approach has been utilized to conduct this research.